2012
DOI: 10.1242/bio.20121750
|View full text |Cite
|
Sign up to set email alerts
|

Complex regulation controls Neurogenin3 proteolysis

Abstract: SummaryThe ubiquitin proteasome system (UPS) is known to be responsible for the rapid turnover of many transcription factors, where half-life is held to be critical for regulation of transcriptional activity. However, the stability of key transcriptional regulators of development is often very poorly characterised. Neurogenin 3 (Ngn3) is a basic helix–loop–helix transcription factor that plays a central role in specification and differentiation of endocrine cells of the pancreas and gut, as well as spermatogon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…Ngn3-hemagglutinin (Ngn3-HA) coimmunoprecipitated Flag-tagged Fbw7 isoform-α and, to a lesser extent, isoform-β (Figure 4B, left panel; and vice versa, as shown in the right panel), and endogenous Fbw7 interacted with Ngn3-HA (Figure 4C). Ngn3 is a heavily ubiquitinated protein (Roark et al., 2012), but Ngn3 ubiquitination was strongly reduced in Fbw7 Δ HCT116 cells when compared to congenic Fbw7 wt cells (Figure 4D). In vitro, wild-type (WT) Fbw7–Flag protein complexes promoted efficient ubiquitination of recombinant Ngn3, but the inactive mutant Fbw7α-ΔFbox–Flag did not (Welcker et al., 2004) (Figures 4E and S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Ngn3-hemagglutinin (Ngn3-HA) coimmunoprecipitated Flag-tagged Fbw7 isoform-α and, to a lesser extent, isoform-β (Figure 4B, left panel; and vice versa, as shown in the right panel), and endogenous Fbw7 interacted with Ngn3-HA (Figure 4C). Ngn3 is a heavily ubiquitinated protein (Roark et al., 2012), but Ngn3 ubiquitination was strongly reduced in Fbw7 Δ HCT116 cells when compared to congenic Fbw7 wt cells (Figure 4D). In vitro, wild-type (WT) Fbw7–Flag protein complexes promoted efficient ubiquitination of recombinant Ngn3, but the inactive mutant Fbw7α-ΔFbox–Flag did not (Welcker et al., 2004) (Figures 4E and S4A).…”
Section: Resultsmentioning
confidence: 99%
“…Id regulates E in diverse developmental and physiological processes, and how it regulates E continues to be investigated (Ling et al 2014;Miyazaki et al 2015). In addition, in some contexts, E proteins may stabilize their dimerization partners (Viñals et al 2004;Roark et al 2012). In this study, we made the novel observation that dimer formation can instead promote bHLH protein instability.…”
mentioning
confidence: 84%
“…Neurog3 has been shown to be inherently unstable and subject to the same ubiquitylation-mediated degradation mechanisms as Neurog2 (Roark et al 2012;Qu et al 2013). These striking parallels for Neurog2 and Neurog3 predict that low levels of unstable Neurog3 activate a subset of target genes specifically associated with promoting progenitor maintenance and the endocrine-biased state.…”
Section: In Our Neurog3mentioning
confidence: 99%
“…4; Supplemental Table S3). Moreover, enforcing G1-like conditions with the Cdki p27Kip1 led to significantly increased Neurog3 stability (Roark et al 2012). In the Neurog3 HI state, Neurog3 promotes expression of the Cdki Cdkn1a (Miyatsuka et al 2011), confirmed by our qRT-PCR analysis, creating a positive feed-forward loop driving cell cycle exit.…”
Section: In Our Neurog3mentioning
confidence: 99%